Transcranial Direct Current Stimulation (tDCS): A Beginner's Guide for Design and Implementation - Thair, Hayley; Holloway, Amy L.; Newport, Roger; Smith, Alastair D. (Frontiers in Neuroscience, 2017)
Transcranial direct current stimulation (tDCS) is a popular brain stimulation method that is used to modulate cortical excitability, producing facilitatory or inhibitory effects upon a variety of behaviours. There is, however, a current lack of consensus between studies, with many results suggesting that polarity-specific effects are difficult to obtain. This article explores some of these differences and highlights the experimental parameters that may underlie their occurrence. We provide a general, practical snapshot of tDCS methodology, including what it is used for, how to use it, and considerations for designing an effective and safe experiment. Our aim is to equip researchers who are new to tDCS with the essential knowledge so that they can make informed and well-rounded decisions when designing and running successful experiments. By summarising the varied approaches, stimulation parameters, and outcomes, this article should help inform future tDCS research in a variety of fields.